2006
DOI: 10.1007/s00167-006-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

CT changes after trochleoplasty for symptomatic trochlear dysplasia

Abstract: Trochlear dysplasia is an important risk factor for patellar instability. Because of a decreased trochlear depth in combination with a low lateral femoral condyle, the patella cannot engage properly in the trochlea. Trochleoplasty is a surgical procedure, which strives to correct such bony abnormalities. The aim of this study was to describe morphological features of trochlear dysplasia and the corrective changes after trochleoplasty on CT scan. The study group consists of 17 knees with trochlear dysplasia hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 36 publications
3
71
0
3
Order By: Relevance
“…Fucentese et al [9] have shown similar results for trochleoplasty patients. They reported that trochleoplasty leads to normal patellofemoral anatomy by correction of the pathological characteristics.…”
Section: Discussionsupporting
confidence: 67%
“…Fucentese et al [9] have shown similar results for trochleoplasty patients. They reported that trochleoplasty leads to normal patellofemoral anatomy by correction of the pathological characteristics.…”
Section: Discussionsupporting
confidence: 67%
“…Computed tomography (CT) scans have been used for measuring lateral trochlear inclination [10]. However, when possible etiologic factors of anterior knee pain is the concern, MRI seems to be more useful than CT to make specific diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The medialized groove causes the tibial tubercle-trochlear groove distance to increase, the low lateral inclination angle decreases the osseous stability, and the tilt occurs as a consequence of the patella articulation with the lateral facet only. 6 The trochleoplasty procedure seems to more or less normalize these anatomical issues 7 and correspondingly it provides good clinical results. This is illustrated by multiple studies in which improvements in patella stability, reduction of anterior knee pain (AKP), and better quality of life have been shown compared with other surgical procedures in cases with severe trochlear dysplasia.…”
mentioning
confidence: 99%